ANALYZING THE LANGUAGE USED BY FITZGERALD IN HIS NOVELS AND SHORT STORIES - Bekmurodova E'zoza Bayramali qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article delves into the captivating language employed by F. Scott Fitzgerald in his renowned novels and short stories. Fitzgerald, a master of the written word, crafted his literary works with meticulous attention to detail, creating a unique and mesmerizing narrative style. Through a comprehensive analysis of Fitzgerald's language, this article aims to uncover the underlying themes, symbolism, and character development embedded in his texts. By examining the eloquence and richness of Fitzgerald's prose, we gain insights into the social, cultural, and psychological complexities of the Jazz Age and the characters who inhabited his fictional world. This study not only highlights the literary genius of Fitzgerald but also offers a deeper understanding of the power of language and its ability to shape and convey meaning in storytelling.